Analysis of the following effect of the natural enemies with Frankliniella intonsa in tea garden. Issue 8 (17th August 2022) - Cheng, Honghao; Chen, Shiyan; Wu, Xiaomeng; Xu, Yue; Zhang, Lin; Sun, Jiazhao; Zhou, Xiazhi; Zou, Yunding; Bi, Shoudong
Abstract: In order to reasonably protect and utilize natural enemies for comprehensive control of Frankliniella intonsa, a systematic investigation was conducted on F. intonsa and natural enemies in tea gardens in Hefei, Anhui Province, and the spatial following effect of natural enemies on F. intonsa was studied. The semi‐variogram of natural enemies and thrips was obtained by the geostatistics method, and the correlation degree between them was analyzed by the grey correlation degree analysis method. The higher the correlation degree between natural enemies and F. intonsa, the closer the relationship between natural enemies and F. intonsa was. In this study, we analyzed the relationship between 11 natural enemies of F. intonsa in tea gardens from October 28, 2020 to November 20, 2020 and from August 22, 2021 to November 19, 2021. The top five natural enemies with the largest closeness index to F. intonsa in Huangshan Dayezhong tea garden are Oxyopes sertatus, Theridion octomaculatum, Plexippus setipes, Xysticus ephippiafus and Erigonidium graminicolum . The top five natural enemies with the largest closeness index to F. intonsa in Pingyang Tezao tea garden are Erigonidium graminicolum, Plexippus setipes, Xysticus ephippiafus, Oxyopes sertatus and Clubiona japonicola . Among the top five natural enemies in the two tea gardens, those in common are Oxyopes sertatus, Erigonidium graminicolum, Xysticus ephippiafus and Plexippus setipes . According to the summation of the closeness index and the sum of the serial numbers, the top five natural enemies closely related to the spatial following of F. intonsa in the tea gardens were Oxyopes sertatus, Plexippus setipes, Erigonidium graminicolum, Xysticus ephippiafus and Theridion octomaculatum . One of the factors closely related to the space of F. intonsa in the same tea garden was the ratio of F. intonsa to a certain natural enemy. The smaller the ratio was, the closer the following relationship was. The results of this study provide scientific basis for biological control and natural enemy protection of F. intonsa .